An interim analysis of the Turkish Myeloma Registry among patients who have received up to two lines of therapy - Sevindik, Omur Gokmen; Ozkurt, Zubeyde Nur; Boga, Can; Besisik, Sevgi Kalayoglu; Ipek, Yildiz; Geduk, Ayfer; Ozsan, Guner Hayri (Cig Media Group, Lp, 2021)
[Abstract Not Available]